2012
DOI: 10.1038/emboj.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

miR-124-regulated RhoG reduces neuronal process complexity via ELMO/Dock180/Rac1 and Cdc42 signalling

Abstract: Little is known about the cellular physiology of Escherichia coli at high cell densities (e.g., greater than 50 g [dry cell weight] per liter), particularly in relation to the cellular response to different growth conditions. E. coli W3100 cultures were grown under identical physical and nutritional conditions, by using a computercontrolled fermentation system which maintains the glucose concentration at 0.5 g/liter, to high cell densities at pH values of 6.0, 6.5, 7.0, and 7.5. The data suggest a relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
101
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(110 citation statements)
references
References 61 publications
7
101
2
Order By: Relevance
“…In support of this, it has been reported that brain-derived neurotrophic factor (BDNF)-induced axonal branching in the developing mouse retina depends on increased levels of miR-132, which promotes axonal branching by inhibiting the translation of its known target Rho family GTPaseactivating protein, p250GAP (Arhgap32) (Marler et al, 2014). Increased levels of other miRNAs, such as miR-124 in hippocampal neurons (Franke et al, 2012) and miR-29a in cortical neurons (Li et al, 2014), can also induce axonal branching. miRNAs are also involved in the directional growth of axons, a process known as axon guidance.…”
Section: Neuronal Polarization Axon Pathfinding and Dendritogenesismentioning
confidence: 89%
“…In support of this, it has been reported that brain-derived neurotrophic factor (BDNF)-induced axonal branching in the developing mouse retina depends on increased levels of miR-132, which promotes axonal branching by inhibiting the translation of its known target Rho family GTPaseactivating protein, p250GAP (Arhgap32) (Marler et al, 2014). Increased levels of other miRNAs, such as miR-124 in hippocampal neurons (Franke et al, 2012) and miR-29a in cortical neurons (Li et al, 2014), can also induce axonal branching. miRNAs are also involved in the directional growth of axons, a process known as axon guidance.…”
Section: Neuronal Polarization Axon Pathfinding and Dendritogenesismentioning
confidence: 89%
“…Protein levels were investigated using Western blot analysis after 2 or 3 d, as described by Carvalho et al (2006). Figure 3 shows the results from a set of experiments using 10 g of DNA after 3 d in culture.…”
Section: Methodsmentioning
confidence: 99%
“…Chick and mouse primary retinal cultures were generated as described previously (Marler et al, 2008). In brief, for mouse cultures, embryonic day 15.5 (E15.5) to E16.5 mouse embryos from timed-mated CD-1 mice were used, with the day of the plug counted as E0.5.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…An elegant study by Sanuki et al showed that miR-124 regulates axon development by inhibiting LIM/homeobox protein 2 (Lhx2) expression in vivo [13] . Another report demonstrated that miR-124 controls axon growth by targeting mRNA of small GTPase RhoG [14] .…”
Section: Mirnas In Axonal Developmentmentioning
confidence: 99%